Consecutive catalytic steps of viral RNA polymerase and exonuclease suggest a way to overcome intrinsic nucleotide analogue resistance - Ashleigh Shannon; Véronique Fattorini; Candice Sartre; Aurélie Chazot; Adel Moussa; Jean-Pierre Sommadossi; Yingxiao Zhu; Manfu Wang; Hui Shi; François Ferron; Karine Alvarez; Bruno Canard (Proceedings of the National Academy of Sciences, 2026)
Nucleotide analogues (NAs) have been successfully used for the treatment of various RNA virus infections by selectively targeting the viral RNA-dependent RNA polymerase (RdRp) for incorporation into the viral genome. However two major families of human-infecting RNA viruses, Coronaviridae (CoV) and Arenaviridae, encode exonuclease domains that may recognize and remove incorporated NAs, thus providing natural resistance against some of these drugs. Both polymerization and excision reactions are mechanistically centered on the nucleotide α-phosphate, enabling the potential for sequential inhibition of both RNA synthesis and repair. Here, we provide structural evidence of inversion of configuration at the phosphorus center during polymerization, demonstrating that the SARS-CoV-2 RdRp proceeds through an S N 2 mechanism. A 2.39 Å resolution cryo-EM structure of a ternary replication complex bound to RNA and an α-thio–modified NTP shows that incorporation of the preferred S P isomer at the 3′ end of the RNA yields a phosphorothioate linkage in the R P configuration. This R P -phosphorothioate RNA product shows reduced cleavage by both the SARS-CoV-2 and three arenavirus RNA exonucleases, revealing a stereochemical preference opposite to that of structurally related DNA exonucleases. This observation contradicts the prevailing assumption that sulfur substitution at the metal-coordinating oxygen universally blocks catalysis. Instead, RNA exonuclease stereoselectivity appears to be shaped not only by metal–sulfur interactions but also by the geometry of nucleophile activation. These findings provide mechanistic insights into phosphoryl transfer in viral polymerases and exonucleases and highlight opportunities to counteract intrinsic nuclease-mediated resistance against antiviral nucleotide analogues.